The Influence of Kinesthetics and Learning Motivation on Volleyball Smash Results in Students of SMP Negeri 1 Buay Madang - Sanopa, Dedi Fuad Tutorial; Rosani, Meilia; Akhbar, M Taheri (Journal of Social Work and Science Education, 2023)
This study investigated the effect of learning motivation on the results of volleyball smashes in SMPN 1 Buay Madang students. Due to the lack of enthusiasm to move, the child needs to be more inspired. This, of course, weakens the physical condition that is less supportive, plus the student’s learning motivation is still deficient when doing volleyball smashes. One type of research is literature research, often called literature research. The descriptive analysis of the study is such that the reader will understand it well. The data used in this study is additional information obtained from the results of research conducted by previous researchers. The data collection method used in this study is the recording or documentation method. The data analysis used in this article is an annotated bibliographic analysis. Based on the literature review, learning motivation affects volleyball learning outcomes. Supporting factors include the role of parents, teachers, and the environment and appropriate opportunities.